Imitation to innovation - LEE, Eunchong (KDI School, 2015)
The Korean government started the construction of Daedeok Science Town in 1973 after recognizing that the Korean industrial structure based on a few conglomerates revealed certain vulnerabilities with the slowdown of the world economy and the rise of international currency and trade pressures. With the increasing importance of regional clusters of sustainable development over the last few decades, the Dadeok Science Town was re-designed as Daedeok Innopolis (DI) in 2006 in pursuance of the Special Act on Fostering Daedeok Innopolis enacted in July, 2005 (www.innopolis.co.kr). The purpose of this qualitative research is to explore and understand the role of governments in regional cluster formation through a case study of the Korean government’s role in the development history and current status of DI. By constructively analyzing a series of literature and quantitative studies on regional clusters and on DI, this paper finds that while the Korean government successfully achieved many of the pre-requisites for establishing a vibrant regional cluster including human capital, infrastructure, technology, and competitive research institutes, it efforts had limitations in promoting other critical components of regional clusters such as intensive inter-firm interaction, shared know-how, spill-over expertise, and strong firm-support systems. This is because these “software” elements grow “organically” over time in a social-capital abundant environment. Lee refers this to an “innovative habitat,” which not only includes “people, firms and institutions – their networks and modes of interaction” but also their complex, dynamic and interdependent relationships which the state has little control over (Lee et al. 2000, 4). While the government has limitations in directly facilitating networks among entities and individuals it can support the next stage of DI’s innovative system by strengthening mechanisms to promote social capital and social trust. Although there is still very little research conducted on “what works” in the promotion of social capital, in general, the realm of civil society is regarded as the most fundamental in the building of the attitudinal aspects of social capital, such as trust and cooperation (Stolle 2003, 20).
Thesis(Master) --KDI School:Master of Development Policy,2015